Gobernanza indirecta de crisis transnacionales: la OPS y la OMS frente a la pandemia de Covid-19 en América Latina - Zamudio González, Laura (El Colegio de México A.C., 2021)
Inter-governmental, regional and international organizations play an active role in the governance of transnational crises. In the context of the Covid-19 pandemic in Latin America, the World Health Organization (who) and the Pan-American Health Organization (paho) have been linked with multiple actors and levels of decision-making, putting into practice what the literature on global governance refers to as indirect governance by orchestration. The article shows that, in practice, the mechanisms of orchestration have established heterogeneous models of coordination and action that, in situations of transnational crisis, allow these organizations to bring together resources, capacities and authority.